Pengaruh Dimensi Sensory Experience Terhadap Revisit Intention: Studi Pada Konsumen Singgah Coffee and Eatery Padang - Putri, Amanda; Surenda, Rian; Andres, Fran Serano (Departemen Pariwisata Universitas Negeri Padang, 2024)
This research aims to describe the sensory experiences associated with revisit intentions. The study benefits from utilizing five sensory experience indicators sight, sound, smell, touch, and taste to enhance consumer revisit intentions. The methodology applied is a quantitative descriptive approach combined with causal associative techniques. Conducted in July 2024 at Singgah Coffee and Eatery, the research focuses on consumers who have visited in the past six months. Samples were gathered using a non-probability sampling method, targeting individuals aged 17 and above who have visited Singgah Coffee and Eatery at least once. The data type collected is primary data, obtained through the distribution of pre-prepared questionnaires. A Likert scale was employed in the development of the research instrument, featuring positively framed statements. The findings indicate that sensory experiences significantly influence customers’ desire to return to Singgah Coffee and Eatery.